EMERGING ANTIMICROBIAL RESISTANCE IN HOSPITAL A THREAT TO PUBLIC HEALTH - Rastogi, Vichal; Mishra, Pankaj Kumar; Bhatia, Shalini (Indian Journal of Community Health, 2012)
Background: Antimicrobial resistance(AMR) threatens the health of many throughout the world, since both old and new infectious diseases remain a formidable public health threat. When pathogenic microorganisms can multiply beyond some critical mass in the face of invading antimicrobials, treatment outcome is compromised. This phenomenon is referred as antimicrobial resistance (AMR). Objective: This retrospective study was conducted to assess the overall antimicrobial resistance in bacterial isolates from tertiary care hospitals as majority of patients here receive empirical antibiotics therapy. Method: This retrospective study was carried out in teaching hospital, Greater Noida to determine prevalence of multidrug resistance in patients in relation to empirical antibiotic therapy in hospital. Various samples (pus,urine,blood) were collected for bacterial culture and antibiotic sensitivity. Results: Total 500 bacterial strains isolated from ICU, surgery, obstetrics & gynaecology and orthopaedics and their sensitivity pattern was compared in this study. The highest number of resistant bacterias were of pseudomonas sp. i.e. 21(33.87%) followed by 16(25.80%) of staphylococcus aureus, 12(19.35%) of Escherichia coli, Klebseilla sp & Proteus vulgaris were 05(8.06%) each & Citrobacter sp. 03(4.83%). Total 62(12.4%) bacterial isolates were found to be resistant to multiple drugs. The 31 (50%) of these resistant bacteria were prevalent in ICU, 12(19.35%) in Surgery, 11(17.74%) in Gynaecology, 08(12.90%) in Orthopaedics.. All the bacterial strains were resistant to common antibiotics like Penicillin, Amoxicillin, Doxycycline & Cotrimoxazole and some were even resistant to Imipenem. Conclusion: Therefore we have outlined the nature of the antimicrobial resistance problem as an important health issue for national and international community. It is advised to avoid use of empirical antibiotics therapy.